Dance movement therapy in rehabilitation of Parkinson's disease – A feasibility study. (April 2021) - Lihala, Shubha; Mitra, Shayori; Neogy, Snehasree; Datta, Noel; Choudhury, Supriyo; Chatterjee, Koustav; Mondal, Banashree; Halder, Saptak; Roy, Akash; Sengupta, Mitul; Kumar, Hrishikesh
Abstract: Introduction: Environmental enrichment during physical exercise was found beneficial in neurological disorders. Application of dance in a structured way could effectively enhance the environment of physical rehabilitation. Therefore, dance therapy can be an alternative exercise program with potential benefit in affect, cognition and social integration in various neurological disorders. Objective: This pre-post experimental study without control was designed to assess the impact of dance movement therapy on cognition, quality of life and motor symptoms in PD patients. Methods: A group of 10 mild-moderate PD patients from Movement Disorders Clinic; I-NK, participated in group sessions for a period of 2 months (twice a week). Each session involved verbal communication followed by warming up movements and concluded with target oriented physical activities, focused on physical symptoms, emotional and cognitive aspects. All the patients were assessed before and after the intervention using Unified Parkinson's Disease Rating Scale part III (UPDRS part III), Hoehn and Yahr Scale (H and Y), Parkinson's Disease Questionnaire 39 (PDQ-39) and Montreal Cognitive Assessment (MOCA). Results: We observed a change in median MOCA score from 19.00 to 22.00 (p .027). PDQ 39 also showed change in median score from 59.50 to 30.00 (p .027). The change in UPDRS III (0.08) and H and Y (0.157) failed to reach significant limit. Conclusion: Dance Movement Therapy was found beneficial in overall cognition and quality of life in patients with mild-moderate PD. Studies with larger sample size will assess the long-term safety and effectiveness of this alternative therapy in future.